Making wise decisions in a smart world responsible leadership in an era of artificial intelligence - Verhezen, Peter 1960- (World Scientific, 2023)
First book that presents an integrated view on benefits and limitations of artificial intelligence (AI) in a corporate world, and how it relates to the distinction of objective descriptive phenomena versus subjective experiences and prescriptive/normative thinking where AI may help us humans to become smarter but not wiser"--